HER-2-Targeted Electrochemical Sensors for Breast Cancer Diagnosis: Basic Principles, Recent Advancements, and Challenges - Leila Kudreyeva; Fatima Kanysh; Aliya Sarsenbayeva; Moldir Abu; Duisek Kamysbayev; Kamilya Kedelbayeva (Biosensors)
In this literature review, methods for the detection of breast cancer biomarkers and the operation of electrochemical sensors are considered. The work of sensors in the determination of breast cancer biomarkers was systematized, a comparative table with other methods was compiled, as was a classification of sensors depending on their intended use. The various traditional methods for the diagnosis of breast cancer biomarkers are described, including mammography, ultrasound, magnetic resonance imaging, positron emission computed tomography, computed tomography, single-photon emission computed tomography, and biopsy, and their advantages and disadvantages are presented. Key sensor parameters for the detection of breast cancer biomarkers are compared, such as the detection limit, linear detection range, response time, sensitivity, and other characteristics depending on the analyte being analyzed. Based on the reviewed scientific papers, the significance of electrochemical sensors in detecting the biomarkers of breast cancer is demonstrated. The types of tumor biomarkers identified by biosensors were analyzed, with a particular focus on HER2. Studies on HER2 detection using electrochemical methods are compared and systematized, and the features of electrochemical biosensors for determining this biomarker are characterized. Possible interfering agents affecting the accuracy of HER2 determination under experimental conditions are considered, their mechanisms of action are analyzed, and ways to eliminate them are proposed. This report provides a summary of the current aspects of scientific research on electrochemical sensors for the detection of breast cancer biomarkers. The development of electrochemical biosensors opens up new prospects for the early diagnosis and prognosis of breast cancer treatment.